PENDAMPINGAN PENGUATAN EKOWISATA PANTAI PENYUSUK MELALUI PENGEMBANGAN E-COMMERCE BERBASIS WEBSITE - Pratiwi, Indah Riezky; Setya Pratama, Muhammad; Sari, Elisa Mayang; Novitasari, Novitasari; Ainin, Dewi Tumatul; Mubaroh, Sari; Rianto, Jimmy; Hardiansyah, Naza (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Penyusuk Beach is one of the panoramic beach tourism destinations on Bangka Island. The beauty of the beach panorama that is highlighted by Penusuk Beach has not been able to attract tourists optimally. This is because the attraction of tourists is lacking for the tour packages offered, the development plan that promotes ecotourism has not been realized, and product marketing has not been effective. The Polman Babel Community Service (PkM) Team carries the theme of strengthening digital marketing-based ecotourism for Penyusuk Beach through the development of a tourism website that will be used by HKm Penyusuk Permai in optimizing the Penyusuk Beach tourist destination. This PkM activity began with an initial discussion stage with partners to explore partner problems and continued with the PkM team discussion stage with students regarding website development, website development, PkM Team discussion with partners (website revision), training on the use and management of the website, to the stage of handover of the website from the PkM team to the partner. Before the training activity, the HKm Penyusuk Permai management was given questions regarding competence in the use and management of the website, as well as a posttest after the training activity was given. Based on the results of the pretest and posttest given, information was obtained that there was an increase in competence in terms of website use and management by HKm administrators by 67%. Through all stages of this PkM activity, it is hoped that HKm administrators can maximize the promotion of Penyusuk Beach tourism in an effort to strengthen ecotourism through the use of websites at Penyusuk Beach.